GAMBARAN PENGGUNAAN ANTIVIRUS PADA PASIEN COVID-19 DI RUANG ICU RSUD ULIN BANJARMASIN - Nirmala, Anisa Feby Insan; Rahmiati, Rahmiati; Nur’Amin, Hendra Wana; Nurrasyidah, Ira; Yasmina, Alfi (Universitas Lambung Mangkurat, 2023)
Antivirus is one of the main therapies for COVID-19. Patients with COVID-19 who need to be transferred to the ICU are those who are seriously ill to critically ill. The purpose of this study was to describe the use of antivirals in COVID-19 patients in the ICU room at Ulin Hospital, Banjarmasin. This study was necessary because no antiviral has been proven effective and specific yet for COVID-19 therapy, the high rate of spread of COVID-19 over the last two years, the large number of cases requiring ICU care, the risk of using antivirals in COVID-19 patients who have certain comorbidities, and this study had never been done before. This study used a descriptive observational study design with ICU patients aged >18 years who were given COVID-19 antiviral therapy with complete electronic data records and/or medical records in the 2020-2021 period. This study found 59 subjects with antivirals used included remdesevir (52.54%), lopinavir+ritonavir (22.03%), favipiravir (15.25%), and oseltamivir (10.16%). Most of the patients were 46-65 years and used remdesevir (50%). Based on gender, both male and female patients used remdesevir (52.54%) as the antiviral. The most common comorbidities were hypertension with remdesevir (42.30%). Based on the duration of hospitalization, the longest duration of hospitalization was remdesevir with an average of 8.74 days.